LUNG CLEARANCE INDEX - USEFUL PARAMETER FOR ASSESSING LUNG FUNCTION IN CYSTIC FIBROSIS CHILDREN - Mihaela Dediu; Ioana Mihaiela Ciuca; Voicu Tudorache; Liviu Laurentiu Pop (Amaltea Medical Publishing House, 2019)
CF is a polymorphic disease whose evolution is marked by pulmonary pathology. Distal obstruction, demonstrated anatomopathological, can be evidenced by spirometry, which can only be used in certain age groups. Early detection of obstruction with appropriate therapy is essential to prolong the life expectancy of these patients. A promising parameter has been described relatively recently, lung clearance index obtained by the multiple wash-out technique. Several studies have demonstrated its efficacy and correlation with pulmonary morphological changes, pointing out that LCI is a feasible and specific parameter to detect small-age lung changes in the CF patient. In conclusion, lung clearance index is a specific parameter for the detection of cystic fibrosis pneumopathy and is currently the standard way to monitor CF pneumopathy, and in future to be used in the current practice of CF centers.